Performance of a two-dimensional position sensitive MRPC prototype with adjustable transmission line impedance - Petriş, Mariana; Deppner, Ingo Martin; Herrmann, Norbert; Simon, Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
The free streaming readout concept of the CBM experiment imposes to the Multi-Strip Multi-Gap RPCs (MSMGRPCs) developed for the CBM-TOF wall a very good matching of the characteristic impedance of the signal transmission line (corresponding to a single strip) to the input impedance of the front-end electronics in order to reduce fake signals produced by reflections. The design of the MSMGRPC prototype described here exploits in an innovative way the advantage of a strip structure for the readout and the high voltage electrodes, the impedance of the signal transmission line being adjusted independent of the detector granularity. The new design allows to built MSMGRPCs with the impedance corresponding to a single strip matched to the input impedance of the front end electronics. The prototype was tested in-beam at CERN-SPS with reaction products of a 30⋅A GeV Pb beam colliding onto a Pb target, in conditions rather similar in terms of energy and multiplicity with those expected at SIS100/FAIR. The obtained performance of 62 ± 3 ps system time resolution and 97% efficiency shows that the new developed prototype meets the challenging requirements for the inner zone of the CBM-TOF wall.